ER Bodies Are Induced by Pseudomonas syringae and Negatively Regulate Immunity. - Rufián Plaza, José Sebastián; Elmore, James M.; Rodríguez-Bejarano, Eduardo; Beuzón-López, Carmen del Rosario; Coaker, Gitta (APS, 2021)
ER bodies are endoplasmic reticulum–derived organelles present in plants belonging to the Brassicales order. In Arabidopsis thaliana, ER bodies are ubiquitous in cotyledons and roots and are present only in certain cell types in rosette leaves. However, both wounding and jasmonic acid treatment induce the formation of ER bodies in leaves. Formation of this structure is dependent on the transcription factor NAI1. The main components of the ER bodies are β-glucosidases (BGLUs), enzymes that hydrolyze specialized compounds. In Arabidopsis, PYK10 (BGLU23) and BGLU18 are the most abundant ER body proteins. In this work, we found that ER bodies are downregulated as a consequence of the immune responses induced by bacterial flagellin perception. Arabidopsis mutants defective in ER body formation show enhanced responses upon flagellin perception and enhanced resistance to bacterial infections. Furthermore, the bacterial toxin coronatine induces the formation of de novo ER bodies in leaves and its virulence function is partially dependent on this structure. Finally, we show that performance of the polyphagous beet armyworm herbivore Spodoptera exigua increases in plants lacking ER bodies. Altogether, we provide new evidence for the role of the ER bodies in plant immune responses.
Keywords: Bacterias fitopatógenas; Inmunología vegetal; Orgánulos celulares; Inmunidad en plantas; ER bodies; Pseudomonas syringae